REPOSISI PERAN PUSTAKAWAN DALAM IMPLEMENTASI TEKNOLOGI INFORMASI DI PERPUSTAKAAN - Hapsari, Dian (Edulib, 2012)
Library at this time has grown more and more rapidly. The presence of information technology, eliminate the library would not have to change with the development of information technology itself. Librarians are the dominant factor in determining the success of a library required to have special competencies in order to synergize with the presence of information technology in the library. In this era of information technology, librarians can be the enlightening agent and the auxiliary act of building a better civilization. Thus, it is expected the library can continue to exist in the era of information technology.